Model and fitting results for the filamentary conduction in MIM resistive switching devices - Palumbo, Félix Roberto Mario (2011)
Experimental results for the resistive switching effect occurring in Pt/HfO2/Pt devices are analyzed within the framework of the two-terminal Landauer theory for mesoscopic conducting systems. It is shown that the magnitude of the current and the voltage dependence of the switching conduction characteristic are mainly dictated by the size of the filamentary path generated after electroforming. The temperature dependence of the high resistance conduction characteristics is also modeled in a consistent manner with the proposed picture.